Efficacy of Olmesartan/Amlodipine Single‐Pill Combination on 24‐h Mean Systolic Blood Pressure Measured by Ambulatory Monitoring in Non‐Responders to Valsartan or Candesartan Monotherapy - Woo‐Baek Chung; Sang‐Hyun Ihm; Yun‐Seok Choi; Ho‐Joong Youn (The Journal of Clinical Hypertension)
ABSTRACT The aim of this study was to evaluate the efficacy of olmesartan/amlodipine (OLM/AML) single‐pill combination (SPC) therapy using ambulatory blood pressure monitoring (ABPM) in non‐responders to valsartan or candesartan monotherapy. Isolated systolic hypertension (ISH) is the most prevalent form of hypertension in middle‐aged and elderly individuals. Patients aged over 55 years who did not achieve the target systolic blood pressure (SBP < 140 mmHg) with valsartan 80 mg or candesartan 8 mg for at least 4 weeks were included. Doses were escalated from 20/5 mg to 40/5 mg and finally to 40/10 mg of OLM/AML SPC until patients reached the target SBP. Efficacy was assessed via ABPM by comparing baseline values with those in the 12th week. Office blood pressure (OBP) and brachial‐ankle pulse wave velocity (baPWV) were assessed at baseline, weeks 4, 8, and 12. Fifty‐four patients (average age 64 ± 6 years; 33 males) participated. The 24‐h mean BPs decreased significantly from an average of 146.2 ± 12.7/93.3 ± 9.2 mmHg to 129.7 ± 14.3/83.4 ± 10.7 mmHg (p < 0.001), and pulse pressures (PPs) from ABPM were reduced (p < 0.001). Additionally, significant reductions in night‐time SBP standard deviations (SDs) (14.7 ± 4.7 vs. 12.5 ± 3.9, p = 0.029) were observed at 12 weeks compared to baseline. OBPs significantly dropped from 151.1 ± 9.7/89.3 ± 8.3 mmHg to 125.5 ± 13.8/77.8 ± 8.8 mmHg after 12 weeks of SPC therapy (p < 0.001). Reductions in PPs of OBP and baPWVs were also observed. OLM/AML SPC therapy effectively reduced the 24‐h mean BP, as measured by ABPM, in hypertensive patients over 55 years old who failed to achieve a target SBP (< 140 mmHg) with angiotensin receptor blocker (ARB) monotherapy using valsartan 80 mg or candesartan 8 mg. Trial Registration: ClinicalTrials.gov identifier: NCT01713920